2016
DOI: 10.1007/s00203-016-1245-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparison and taxonomic relatedness of multiple Xylella fastidiosa strains reveal the occurrence of three subspecies and a new Xylella species

Abstract: A total of 21 Xylella fastidiosa strains were assessed by comparing their genomes to infer their taxonomic relationships. The whole-genome-based average nucleotide identity and tetranucleotide frequency correlation coefficient analyses were performed. In addition, a consensus tree based on comparisons of 956 core gene families, and a genome-wide phylogenetic tree and a Neighbor-net network were constructed with 820,088 nucleotides (i.e., approximately 30-33 % of the entire X. fastidiosa genome). All approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 46 publications
6
63
0
1
Order By: Relevance
“…For instance, strains collected from a single host and geographic location formed different haplotypes when they were analyzed by MLSA of environmentally mediated genes (Parker et al 2012). Interestingly, studies that detected genetic diversity among X. fastidiosa strains have also reported the presence of homologous recombination (HR) Coletta-Filho et al 2017;Marcelletti and Scortichini 2016;Nunney et al 2010Nunney et al , 20122013, 2014a andScally et al 2005). In fact, HR was predicted to have a greater effect in creating genetic diversity in X. fastidiosa than point mutation (Kung et al 2013; Nucleotide sequence data is available in the GenBank database under accession numbers KY616728 to KY616749.…”
mentioning
confidence: 99%
“…For instance, strains collected from a single host and geographic location formed different haplotypes when they were analyzed by MLSA of environmentally mediated genes (Parker et al 2012). Interestingly, studies that detected genetic diversity among X. fastidiosa strains have also reported the presence of homologous recombination (HR) Coletta-Filho et al 2017;Marcelletti and Scortichini 2016;Nunney et al 2010Nunney et al , 20122013, 2014a andScally et al 2005). In fact, HR was predicted to have a greater effect in creating genetic diversity in X. fastidiosa than point mutation (Kung et al 2013; Nucleotide sequence data is available in the GenBank database under accession numbers KY616728 to KY616749.…”
mentioning
confidence: 99%
“…Sets of genes involved in important functions can be compared and studied (da Silva et al, 2007; Barbosa et al, 2015), SNPs can be identified and PCR primers can be designed for the identification of specific strains (Doddapaneni et al, 2006; Marcelletti and Scortichini, 2016b) and detailed phylogenetic analysis can be performed. As an example, by genome-wide comparison of 21 X. fastidiosa strains, Marcelletti and Scortichini (2016a) constructed a phylogenetic tree analyzing 820,088 nucleotides, ~30% of the entire X. fastidiosa genome. According to their results, three different, clearly defined subspecies of X: fastidiosa can be identified, while the two subsp.…”
Section: Hosts and Diseasesmentioning
confidence: 99%
“…sandyi and morus are actually members of the subsp. fastidiosa (Marcelletti and Scortichini, 2016a). Although extremely powerful, the whole genome analysis is still a time-consuming and relatively expensive technique that cannot be considered an applicable method for a fast identification of pathogens, especially in field applications.…”
Section: Hosts and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since subsp. pauca is a frequently reported subspecies (as well as sandyi, tashke, or morus), only fastidiosa and multiplex are so far considered valid names by the International Society of Plant Pathology Committee on the Taxonomy of Plant Pathogenic Bacteria (ISPP-CTPPB) [39], and a revision was recently proposed [40].…”
Section: Pathogen/host Interactionmentioning
confidence: 99%